Vending machines for reducing harm associated with substance use and use disorders, and co-occurring conditions: a systematic review - Alice Zhang; Matthew Carrillo; Ryan Liu; Sarah M. Ballard; Alexis Reedy-Cooper; Aleksandra E. Zgierska (Harm Reduction Journal)
Abstract Background To stem rising fatal overdoses and other substance use/use disorder (SUD)-related harms, communities are turning to low-barrier harm reduction strategies, such as harm reduction-focused vending machines (VMs) that distribute naloxone, fentanyl test strips, and other harm reduction-related items. This systematic review aims to synthesize literature on VMs for SUD-related harm reduction. Methods Four databases (Embase, Cochrane, PubMed, MEDLINE) were searched from their inception through November 29, 2023. References of identified eligible articles and pertinent prior reviews were also searched for relevant eligible research articles describing VM’s feasibility, acceptability, reach, and/or impact when used for SUD-related harm reduction. Data from eligible articles were systematically extracted and summarized. Results The search found 45 eligible articles covering 30 separate studies involving 191,242 participants (190,576 VM users; 666 non-users). Most studies were conducted outside of the U.S. (n = 20), focused on individuals who injected drugs (n = 18), and evaluated syringe-dispensing VMs (n = 12). Of the 45 articles, the majority evaluated feasibility (n = 35), followed by acceptability (n = 21), impact (n = 17), and reach (n = 14). The feasibility-assessing articles noted high demand for VM-dispensed items, with usage mostly occurring outside of traditional business hours, and more syringes and HIV self-tests being dispensed compared to some in-person programs. The VMs were generally accepted by target populations, regardless of the items dispensed, and reached high-risk populations. Impact evaluation was limited and based on item dispensed. Seven articles examined the impact of syringe-dispensing VMs and described reductions in syringe sharing (n = 4) and drug use (n = 2), as well as stable or declining rates in drug use-related crime (n = 1). Articles evaluating the impact of HIV self-test-dispensing VMs (n = 3) described HIV detection rates ranging from 1.9% to 17.7%. Two articles reported reduced fatal overdoses after naloxone-dispensing VMs were implemented. Discussion VMs show promise as a low-barrier method for reducing SUD-related harm, decreasing health disparities, and engaging hard-to-reach populations. Future implementation science-based research is needed to assess VMs’ impact on individual and community health outcomes, including overdose.